Neoparamoeba perurans is a cosmopolitan aetiological agent of amoebic gill disease - Young, ND; Dykova, I; Snekvik, K; Barbara Nowak; Morrison, RN (2008)
Previously we described a new member of the Neoparamoeba genus, N. perurans, and showed that it is an agent of amoebic gill disease (AGD) of Atlantic salmon Salmo salar cultured in southeast Tasmania, Australia. Given the broad distribution of cases of AGD, we were interested in extending our studies to epizootics in farmed fish from other sites around the world. Oligonucleotide probes that hybridise with the 18S rRNA of N. perurans, N. branchiphila or N. pemaquidensis were used to examine archival samples of AGD in Tasmania as well as samples obtained from 4 host fish species cultured across 6 countries. In archival samples, N. perurans was the only detectable amoeba, confirming that it has been the predominant aetiological agent of AGD in Tasmania since epizootics were first reported. N. perurans was also the exclusive agent of AGD in 4 host species across 6 countries. Together, these data show that N. perurans is a cosmopolitan agent of AGD and, therefore, of significance to the global mariculture industry. Â© Inter-Research 2008.